Evaluation of effectiveness of Letrozole in treatment of infertility in women with polycystic ovary syndrome - Mile, Jasrin Akter; Munni, Mashuma; Rahman, Dilara; Parvin, Tahamina; Pervin, Shanaz (Central Medical College Journal, 2024)
Background: Polycystic ovary syndrome (PCOS) is the most common endocrine and metabolic disease, characterized by hyperandrogenism, oligomenorrhea, and polycystic ovaries. PCOS is one of the most causes that affect the women of childbearing age, and often leads to infertility. Various managements were proposed for infertile women with PCOS. However, the optimal management option has not been addressed satisfied. Although multiple treatments including weight reduction, clomiphene citrate, metformin, gonadotropins, and ovary cauterization have been reported to treat such condition, the efficacy still has insufficient evidence to support. Objectives: Purpose of this study was to evaluate the effectiveness of Letrozole in treatment of infertility in women with polycystic ovary syndrome. Materials & method: This study was carried out to assess the effectiveness of letrozole and on pregnancy outcomes including the ovulation induction, pregnancy rate, and endometrial thickness in infertile women with polycystic ovarian syndrome (PCOS). Total 106 infertile PCOS patients were recruited and allocated in two groups, Group-L (received letrozole at 2.5 mg twice daily on the 3rd–5th days of menstrual cycle for 5 consecutive days), Group-G 75 U/d−1 gonadotropin through intramuscular injection for 5 days starting from the third day of menstrual cycle). All patient in both arm completed treatment and follow-up. Patients in both groups were treated up to 5 treatment cycles. During follow up, transvaginalultrasonogram (TVS) was performed to see the details of the follicles and the endometrium. Data was processed and analysed with the help of computer program SPSS and Microsoft excel. Quantitative data expressed as mean and standard deviation and qualitative data as frequency and percentage. Comparison was done by tabulation and graphical presentation in the form of tables, pie chart, graphs, bar diagrams, histogram & charts etc. Result: Mean age of the patient was 26.3 ± 5.7 years in group-L and 25.9 ± 6.1 years in group-G. There were no statistical significant differences between the 2 groups regarding age, body weight, height, body mass index (BMI). Present study results showed that patients who received letrozole exert better outcomes in primary endpoint, including ovulation rate (86.7% in group-L & 62.2% in group-G, P =0.004), endometrial thickness (9.3 ± 1.1 mm in group-L & 8.5 ± 1.1 mm in group-G, P = 0.003) and pregnancy rate (64.1% in group-L & 30.1% in group-G, P =0.005). Abortion rate (till the end of 12th week) and multiple pregnancy rate were higher in group-G, but result were non-significant in between groups. Live birth rate in the letrozole group was higher 29(54.7%) than group-G 14(26.4%), the difference was statistically significant (P < .05). Conclusion: Patients who took Letrozole had significantly higher endometrial thickness than other group. Due to the higher pregnancy rate and lower incidence of abortion or multiple pregnancy, letrozole can be an effective for the treatment of anovulatory subfertility of the PCOS patients. Central Medical College Journal Vol 7 No 1 January 2023 Page: 13-19